MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS XI SMK DENGAN MODEL PROBLEM BASED LEARNING DAN MEDIA KOMIKA PRO BERBANTUAN GEOGEBRA - Eva Dahlia Sari; Luvy Sylviana Zanthy; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Education is an important aspect that must be implemented in Era 4.0 towards 5.0. The results of the research in one school showed that the students' mathematical critical thinking skills were still low.  This study aims to improve students' mathematical critical thinking skills in class XI Fashion Design. The research method used is descriptive qualitative, namely classroom action research. The subjects who were given the action were students of Class XI Fashion Design at SMK Plus Darussurur Cimahi for the academic year 2021-2022 totaling 30 people and divided into 6 groups. The instrument is in the form of a critical thinking ability test as many as 2 story questions, on the Problem Based Learning Model LKPD which is presented in digital comics pro, assisted by Geogebra. The results showed that there was an increase in learning outcomes from cycle 1 to cycle 2, but in cycle 3 there was a decrease. Overall, the results showed that there was an increase in the tendency of students' mathematical critical thinking abilities, from low to good, good responses and above average mastery.